1985
DOI: 10.1002/etc.5620040202
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of priority pollutant concentrations in the United States using storet database

Abstract: The examination of the 80,000,000 STORET data points for priority pollutant concentrations yielded principles for system usage to determine the individual occurrence of these pollutants in U.S. waterways. A case study on a representative priority pollutant (butyl benzyl phthalate) is presented in detail to highlight the characteristics of the database. The use of data from the 1980s only is recommended, based on the number of data points and the likelihood that better quality assurance practices were employed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In an assessment of STORET data covering the period , Staples et al (1985 reported median concentrations in sediment of ≤500 µg/kg dry weight for 15 PAHs (acenaphthene, have been reported to range from approximately 100 to 11,000 µg/kg dry wt, and 800 to 23,000 µg/kg dry wt, respectively (Demuth et al 1993).…”
Section: Sediment and Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…In an assessment of STORET data covering the period , Staples et al (1985 reported median concentrations in sediment of ≤500 µg/kg dry weight for 15 PAHs (acenaphthene, have been reported to range from approximately 100 to 11,000 µg/kg dry wt, and 800 to 23,000 µg/kg dry wt, respectively (Demuth et al 1993).…”
Section: Sediment and Soilmentioning
confidence: 99%
“…In an assessment of STORET data covering the period , Staples et al (1985 reported median concentrations in biota of In summary of data on tissue contamination in mussels and oysters from the first 3 years (1986)(1987)(1988) of the National Oceanic and Atmospheric Administration (NOAA) Mussel Watch Project, which involved the analysis of samples from 177 coastal and estuarine U.S. sites, overall mean concentrations of low molecular weight PAHs ranged from not detected (detection limits 3.3-67 ng/g dry weight) to 4,200 ng/g dry weight (NOAA 1989). Mean concentrations of low molecular weight PAHs for individual years 1986, 1987, and 1988 ranged up to 9,600, 3,200, and 4,300 ng/g dry weight,…”
Section: Sediment and Soilmentioning
confidence: 99%
“…The median ethylbenzene concentration in ambient surface waters in the United States in 1980-1982 was <5.0 μg/L (ppb) according to EPA's STORET water quality database (Staples et al 1985). The chemical was detected in 10% of the 1,101 samples collected during that period.…”
Section: Watermentioning
confidence: 99%
“…The median ethylbenzene concentration (dry weight) detected in sediment in the United States in 1980-1982 was 5 μg/kg (ppb) according to EPA's STORET water quality database (Staples et al 1985). The Ethylbenzene concentrations were analyzed in contaminated soil samples obtained from the site of a former crude oil and natural gas production facility near Los Angeles, California.…”
Section: Sediment and Soilmentioning
confidence: 99%
See 1 more Smart Citation